Chemical constituents and biological investigations of the aerial parts of Egyptian Clerodendrum inerme - Sabrin R.M. Ibrahim; Khalid Z. Alshali; Mostafa A. Fouad; Ehab S. Elkhayat; Rwaida A. Al Haidari; Gamal A. Mohamed (Faculty of Pharmacy, Cairo University, 2014)
B-friedoolean-5-ene-3-β-ol (1), β-sitosterol (2), stigmasta-5,22,25-trien-3-β-ol (3), betulinic acid (4), and 5-hydroxy-6,7,4'-trimethoxyflavone (5) were isolated from the aerial parts of Clerodendrum inerme L. (Verbenaceae). Their structures were established based on analyses of physical and spectroscopic data. Compounds 1, 4, and 5 were isolated for the first time from the plant. C. inerme L. was known as a rich source of terpenes, sterols, and phenolic compounds, so the antioxidant and anti-inflammatory activities were evaluated. The total methanolic extract (TME) and compound 5 showed scavenging activity with maximum inhibition of 61.84% for TME (100 μg/mL) and 37.19% for 5 (20 μM), respectively, using DPPH assay. In addition, the TME exhibited anti-inflammatory activity more than indomethacin at dose 200 mg/kg using the formalin induced hind paw edema method.